25 agricultural research and extension organizations use novel citizen science approach for scaled validation/diffusion of climatically adapted varieties - CGIAR Research Program on Climate Change, Agriculture and Food Security (2017)
The novel digital citizen science platform ClimMob allows for scaled farmer-participatory validation/diffusion of climatically adapted, stress tolerant varieties of several crops, including wheat, rice, sorghum, groundnut, beans, and barley. The platform has been actively used by over 25 agricultural research/extension organizations to organize adaptive trials, leading to (1) more cost-effective, scalable trials (2) unique climate adaptation insights that could not have been generated otherwise and (3) direct diffusion of a diverse range of varieties to more than 18,000 farmers directly.